Does early identification of work-related stress in primary health care effect pharmacy dispensing?. (30th September 2020) - Bjerkeli, P; Skoglund, I M; Holmgren, K
Abstract: Background: The study is part of a randomised controlled trial with the overall aim to evaluate if use of the Work Stress Questionnaire (WSQ), combined with feedback at consultation, can be used by healthcare professionals in primary health care to prevent sickness absence. The specific aim of the present study was to investigate whether there were differences in pharmacy dispensing of prescription medications between the intervention group and the control group. Methods: The study was a randomized controlled trial. Non-sick-listed employed women and men, aged 18 to 64 years, seeking care at primary health care were eligible participants. The intervention included general practitionerś (GP) training to use the WSQ, early identification of patientś work-related stress by the WSQ, and GPś feedback on the WSQ results during the consultation. Pharmacy dispensing data from the Swedish Prescription Drug Register for 12 months following the intervention were analysed using Mann Whitney U tests and chi-square tests. Primary outcomes were the number of different medications used, type of medication and number of prescribing clinics. Results: The study population included 271 individuals (132 in the intervention group and 139 in the control group). The proportion of individuals who collected more than 10 different medications was higher in the control group than in the intervention group (15.8% versus 4.5%, p = 0.002). In addition, the proportion of individuals filling prescriptions issued from more than three different clinics was higher in the control group than in the intervention group (17.3% versus 6.8%, p = 0.007). The number of different medications used per individual did not differ significantly between the control group (median 4.0) and the intervention group (median 4.0, p-value 0.076). Conclusions: Systematic use of the WSQ combined with training of GPs and feedback at consultation may affect certain aspects of pharmacological treatment in primary health care patients. Key messages: Systematic use of the WSQ combined with training of GPs and feedback at consultation may affect certain aspects of pharmacological treatment in primary health care patients. Patients in the intervention group had less polypharmacy and filled prescriptions issued from a smaller number of different clinics than controls.